Does the length of dental procedure influence children’s behavior during and after treatment? A systematic review and critical appraisal - Jamali, Zahra (J Dent Res Dent Clin Dent Prospects, 2018)
The aim of this systematic review was to investigate the effect of treatment duration on children’s behavior and/or anxiety in the dental setting. To this end, a systematic search was conducted in Pubmed/Medline and Scopus from 1970 to march 2017 for English language articles that assessed the relationship between dental treatment duration or length, and fear/anxiety or behavior in children aged <12 with no confounding medical and/or psychological history and neuro-psychiatric disabilities. Four studies investigating the effect of treatment duration on children’s behavior during and/or after treatment were included. None of the reviewed studies investigated the effect of treatment duration on children’s dental anxiety or fear. There was a general tendency towards deterioration of children’s behavior with an increase in treatment duration. In conclusion, our results undermine the validity of current suggestions about the appropriate treatment duration. Further clinical trials are needed to establish appropriate treatment duration for more effective behavioral management of pediatric patients during dental proce-dures.